Capital flight from the Philippines, 1970-2002 - Beja, Edsel L, Jr (Archīum Ateneo, 2005)
Capital flight is defined as the movement of capital from resource-scarce developing countries to avoid social controls. It is measured as net unrecorded capital outflow, or the residual between officially recorded uses and sources of funds. Total capital flight from the Philippines was estimated at USD 138 billion (in 1995 constant prices) for the period 1970-2002. Including imputed interest earnings, the stock of capital flight as of 2002 was USD 218 billion. Indeed, by any yardstick, these figures are significant amounts of lost resources that could have been utilized to generate additional output and jobs in the country. Were it not for capital flight, the Philippines would have reached an economic performance like the Asian economic tigers.